STATISTICAL ESTIMATION OF IMPACT OF TOTAL CASH ON RUSSIAN AND KAZAKHSTANI ECONOMY - Toty K. Bekzhanova (Статистика и экономика)
A statistical analysis of the size of shadow economy of different countries of the world is given in the article. Use of cash is one of the fundamental reasons of a shadow economy of a state. The author considers the volume of cash in different countries as well as its assessment and the methods of combating cash in Russia and Kazakhstan.